2019
DOI: 10.18621/eurj.432272
|View full text |Cite
|
Sign up to set email alerts
|

The relation between performance and oral health in male athletes

Abstract: Objectives: .Oral health is as important to an athlete's sporting successas regular exercise and adequate nutrition. The aim of this study was to investigate the relation between oral health and sporting performance. Methods: This prospective study was carried out with male athletes. Athletes' demographic characteristics, dental care habits, number of decayed, missing or filled teeth, and sporting performance data were recorded. The Decayed Missing Filled Teeth (DMFT) index, Significant Caries index (SCI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…14 In the sports arena, athletes with the oral disease have revealed that their performance had been affected during training and competition, 15,16 making them feel distressed, 17 impacting their quality of life, 15 and compromising sports achievement. [15][16][17] Currently, the knowledge of healthcare providers about dental trauma prevention and immediate treatment care among sports enthusiasts remains limited. [18][19][20][21] Globally, there are limited epidemiological studies on the awareness of dental injuries of para-athletes, and the findings on Malaysian athletes' oral health status are unprecedented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In the sports arena, athletes with the oral disease have revealed that their performance had been affected during training and competition, 15,16 making them feel distressed, 17 impacting their quality of life, 15 and compromising sports achievement. [15][16][17] Currently, the knowledge of healthcare providers about dental trauma prevention and immediate treatment care among sports enthusiasts remains limited. [18][19][20][21] Globally, there are limited epidemiological studies on the awareness of dental injuries of para-athletes, and the findings on Malaysian athletes' oral health status are unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be attributed to the premature extraction of decayed teeth as a treatment of choice instead of fillings and other restorations. 14 In the sports arena, athletes with the oral disease have revealed that their performance had been affected during training and competition, 15,16 making them feel distressed, 17 impacting their quality of life, 15 and compromising sports achievement. [15][16][17] Currently, the knowledge of healthcare providers about dental trauma prevention and immediate treatment care among sports enthusiasts remains limited.…”
Section: Introductionmentioning
confidence: 99%